Dyspnea in patients treated with P2Y12 receptor antagonists: insights from the GReek AntiPlatElet (GRAPE) registry. (3rd October 2017) - Alexopoulos, Dimitrios; Xanthopoulou, Ioanna; Perperis, Angelos; Goudevenos, John; Hamilos, Michalis; Sitafidis, George; Kanakakis, Ioannis; Vavouranakis, Manolis; Giannopoulos, George; Barampoutis, Nikolaos; Deftereos, Spyridon; Lekakis, John
Abstract: In 'real life' acute coronary syndrome (ACS) patients undergoing percutaneous coronary intervention (PCI) and receiving contemporary antiplatelet treatment, data on dyspnea occurrence and impact on persistence with treatment are scarce. In a prospective, multicenter, cohort study, ACS patients undergoing PCI were recruited into the GReekAntiPlatElet (GRAPE) registry. During 1-year follow up, overall, 249/1989 (12.5%) patients reported dyspnea, more frequently at 1-month and decreasing thereafter. Multivariate analysis showed that ticagrelor administration ( n = 738) at discharge was associated with the occurrence of dyspnea: Odds ratio 2.46 (95% confidence interval, CI, 1.87–3.25), p < 0.001. Older age, lower hematocrit, and prior bleeding event were also associated with dyspnea reports. Persistence, switching, and cessation rates were 68.3%, 20.9%, and 10.8% vs 76.7%, 12.5%, and 10.9% among patients reporting dyspnea compared with those who did not, p for trend = 0.002. In conclusion, in ACS patients undergoing PCI and treated with a P2Y12 receptor antagonist, dyspnea occurs commonly, particularly when ticagrelor is administered. Non-persistence with antiplatelet agents at discharge is more frequently observed among dyspnea-reporters.